2022
DOI: 10.1590/0103-8478cr20201046
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and behavioral response of horses submitted to functional exercises and acupuncture

Abstract: The present research evaluated muscle activation degrees and relaxation of patrolling horses submitted to dynamic mobilization exercises, associated or not with acupuncture. Twelve mixed breed gelding, aged 10 ± 2.0 years, were distributed in three treatments. Treatment with a single session of dynamic mobilization exercises (longitudinal cervical flexion of head between hooves, between carpus and to up to chest); treatment with a single acupuncture session during 20 minutes, and treatment with a single sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The multifidus muscle is classified as a back-stabilizing muscle ( Oliveira et al, 2014 ); therefore, it plays an important role in stabilizing the intervertebral joints, acting as a connection between the spine bones and avoiding micro movements related to the joint surfaces during locomotion. Atrophy of this muscle, as noted in this case series, can result in vertebral instability capable of promoting vertebral pathologies, such as osteoarthritis ( Rodrigues et al, 2021 ). Therefore, it is imperative to develop therapeutic approaches that promote hypertrophy of this muscle.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The multifidus muscle is classified as a back-stabilizing muscle ( Oliveira et al, 2014 ); therefore, it plays an important role in stabilizing the intervertebral joints, acting as a connection between the spine bones and avoiding micro movements related to the joint surfaces during locomotion. Atrophy of this muscle, as noted in this case series, can result in vertebral instability capable of promoting vertebral pathologies, such as osteoarthritis ( Rodrigues et al, 2021 ). Therefore, it is imperative to develop therapeutic approaches that promote hypertrophy of this muscle.…”
Section: Discussionmentioning
confidence: 64%
“…The benefits of adopting a functional exercise-based physical training program have been extensively studied in recent years ( Oliveira et al, 2015 ; Rodrigues et al, 2021 ) and have been shown to be effective in the therapeutic protocol in this series of cases. The observed benefits included increased balance, elasticity, and flexibility of the animals after 30 days of dynamic mobilization exercises, as described by Frick (2010 ).…”
Section: Discussionmentioning
confidence: 99%